Assessment of Benefits Derived from SACDP/IFAD through Community based Participatory Projects in Bodinga Zone - M, Attahiru; Abubakar , B. Z; Barau, A. A (Asian Journal of Agriculture and Rural Development, 2014)
The study was carried out to assess the benefits derived from SACDP/IFAD through community based participatory projects in Bodinga zone. The zone comprises four villages from two local government areas. All the four villages were purposively selected for the study. Eighty (80) respondents were randomly selected and interviewed using structured questionnaire (60 male and 20 female). Data collected was analyzed using frequency and percentages. Results revealed that majority of the respondents are men, married and within their active productive age. Results further show that majority of the respondents have benefitted from one project or the other and have subsequently replicated similar community based initiatives. It is recommended that vigorous efforts be put in place by both donor agencies and government to enhance rural people derivation of benefits from community based participatory projects and participation in self-help initiatives.